A Systematic Review of Digital Media in Enhancing English Language Learning in Indonesian Schools - Alfa Oriza Sativa Muslimawati; Alya Dwi Dirgantini; Nasyila Putri Humaira; Ririn Novayana; Wahyuni (Yayasan Al Hidayah, 2025)
This systematic review aims to comprehensively evaluate the extent to which and how the integration of Digital Media and Information and Communication Technology (ICT) has transformed the process of English Language Learning (ELL) in Indonesian schools, and to identify the most effective digital tools for addressing the common challenges of motivation and the limitations of traditional pedagogy. Utilizing the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) 2020 checklist, this research systematically evaluated recent peer-reviewed articles, primarily sourced from the ERIC database, to understand the role of digital tools, such as mobile applications, interactive games, and social media platforms. The findings reveal that the integration of digital media significantly promotes student engagement and motivation, offers personalized learning experiences, and effectively improves specific language skills, including vocabulary acquisition and writing proficiency. Furthermore, digital media fosters a collaborative learning environment and enhances accessibility. This research underscores the necessity of adapting pedagogical practices to fully leverage the potential of digital media, thereby providing valuable insights for Indonesian educators, curriculum developers, and policymakers in shaping a more effective and relevant English education system for the digital era.